The Effects of Administrative Corruption in Public Office in The Kingdom of Saudi Arabia - Alnafisah, Lina Abdullah; Alyahya, Bariah Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to analyze the concept of administrative corruption and its various forms as outlined in several relevant Saudi regulations, namely: the Anti-Bribery Law, the Penal Law for Forgery Crimes, and the Public Office Penalties Law. The research addresses the legal aspects of these forms by clarifying the legal concepts, elements of the crime, and the conditions required for their establishment, leading up to the penalties stipulated in each regulation. The study seeks to highlight the efforts of the Kingdom of Saudi Arabia in combating administrative corruption through the establishment of the Oversight and Anti-Corruption Authority (Nazaha), while also illustrating the extent of its expanded jurisdiction. The researcher adopted the descriptive-analytical method by describing administrative corruption and its manifestations, and by relying on and analyzing official statistics issued by the Oversight and Anti-Corruption Authority for the years 2019–2023, which indicate that reports related to administrative corruption crimes significantly exceeded those related to financial corruption. The study also analyzes the efforts of the Oversight and Anti-Corruption Authority in addressing this issue.The study concluded that the expansion of the powers and responsibilities of the Oversight and Anti-Corruption Authority, after the integration of several entities into it, led to improved quality of oversight performance and increased effectiveness of the Authority in pursuing administrative corruption. It also found that administrative corruption crimes do not expire due to the passage of time, and that all individuals, regardless of their administrative position, are held accountable for corruption crimes in the Kingdom of Saudi Arabia. The researcher recommended launching a comprehensive national campaign to combat administrative and financial corruption, along with continuing to activate digital media tools to raise awareness and facilitate the dissemination of information to the public.
Keywords: Administrative corruption; public office; Oversight and Anti-Corruption Authority; digital media; public employee; reports